Focusing on probe-modified peptides: a quick and effective method for target identification. Issue 67 (22nd July 2016) - Sun, Huan; Ren, Yan; Hou, Weijie; Li, Lin; Zeng, Fanqi; Li, Sisi; Ma, Yongfen; Liu, Xiao; Chen, She; Zhang, Zhiyuan
Abstract : BTC-ABPP was developed by converting the reactants of a click conjugation from proteins (biochemistry) to peptides (chemistry) to identify the modified peptides. Abstract : A new and efficient method focusing on probe-modified peptides was developed to identify the target protein and modification site of a hit compound or a drug. This method exhibited high click conjugation efficiency and few false-positive results. The modification site further facilitated target validation, biological mechanism study and new indications exploration.